2020
DOI: 10.1186/s12879-020-4919-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological changes in measles infections in southern China between 2009 and 2016: a retrospective database analysis

Abstract: Background: The incidence rate of measles in China reached a nadir in 2012 after 2 supplementary immunization activities (SIAs) were undertaken in 2009 and 2010. However, the disease began re-emerging in 2013, with a high prevalence rate observed in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated that infants aged 0–8 months were too young for routine immunization. The immunity in newborns was temporary and began to wane at 6 months of life, which made infants the most susceptible to rubella [ 42 , 43 ]. Another study found that women of childbearing age had lower levels of rubella antibodies, increasing the risk of congenital rubella syndrome in newborns to some extent [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that infants aged 0–8 months were too young for routine immunization. The immunity in newborns was temporary and began to wane at 6 months of life, which made infants the most susceptible to rubella [ 42 , 43 ]. Another study found that women of childbearing age had lower levels of rubella antibodies, increasing the risk of congenital rubella syndrome in newborns to some extent [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it suggested strengthening routine surveillance of vaccination coverage among migrants (Chong, K. et al, 2020 and in older age group individuals (Nmor, J. C. et al, 2011). Even though great results were achieved by supplementary immunisation activities in providing herd immunity, there was a resurgence of measles cases due to insufficient immunisation coverage among children (Zheng, H. et al, 2020, (Ma, C. et al, 2014.). The study from Myanmar reported an increase in the measles mortality rate since 2016.…”
Section: Discussionmentioning
confidence: 99%
“…While in urban China, routine vaccination services are clustered in community-level health centres and regularly delivered to age-appropriate children. Large-scale measles outbreaks re-emerged in Guangxi of southwest China during 2013–2014, even though Guangxi had achieved ≥95% coverage of routine measles vaccination 34. Most of the reported cases were children who were vaccinated untimely or incompletely.…”
Section: Introductionmentioning
confidence: 99%